Llama Llama Holiday Drama - Dewdney, Anna (New York : Viking, 2010)
Llama Llama becomes overwhelmed as Christmas preparations progress, until his mother reminds him of the real gift the holiday brings.
Keywords: Christmas stories; Llamas -- Juvenile fiction; Mother and child -- Juvenile fiction; Stories in rhyme; Christmas -- Fiction; Mother and child -- Fiction; Llamas -- Fiction